THE RELATIONSHIP AMONG TIME LEARNING MANAGEMENT, STUDENTS INTERACTION WITH TEACHER AND THE USE OF RESOURCES WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII MTs MUHAMMADIYAH GEDONGTENGEN YOGYAKARTA - Desi Hardiyanti; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2017)
Less effective time learning management, less effective students’ interaction with the teacher, and less effective of the use of learning resources were expected to have a relationship to mathematics learning outcomes of the students. This study was aimed to determine the presence or absence of a positive and significant relationship among time learning management, student's interaction with teachers and the use of learning resources with mathematics learning outcomes in students class VIII MTs Muhammadiyah Gedongtengen Yogyakarta odd semester in academic year 2016/2017. The population in this study was all students of class VIII odd semester at MTs Muhammadiyah Gedongtengen Yogyakarta in the academic year of 2016/2017 consisted of 3 classes. While the sample being picked was class VIII C using random sampling technique. The techniques of data collection ware test and nontest. The data collection instruments were collected using questionnaires and test methods. Test research instruments used were validity tests, different power tests, and reliability tests. The prerequisite test used was a normality test, linearity test, and independent test. Analysis of data used product-moment correlation analysis and multiple linear regression analysis. The result showed that there was a positive and significant correlation among time learning management, students interaction with teacher and the use of resources with mathematics learning outcomes, multiple correlation coefficient (R) = 0,6195 with a regression equation at the 5% significance level, obtained at 3,5300 and at 3,20 means . The results of relative contribution were SR = 61,5686%, SR = 5,6148% and SR = 32,8166% and the results of effective contribution were SE = 23,6322%, SE = 2,1552% and SE = 12,5962%.